RELIABILITY ANALYSIS OF NANJUNG TUNNEL - Fajar Somahartadi, Tiko
Nanjung Tunnel is used for shortening the retention time of flooding in Baleendah, Dayeuhkolot and its surroundings. For sustainability purposes therefor reliability analysis is required. Reliability analysis comes from qualitative methode which is two level risk analysis, level 1(Safety factor) and level 2 (First Order and Second Moment) and semiquantitaive method to get risk level. By transforming to normally distributed, the Resistance and Load flow thus resulted in risk and reliability probability. Risk probability is the risk magnitude when applied flow loads. Risk is a cause of actions resulting damage or danger, in other words the probability that can endanger Nanjung Tunnel when applied a flow load to the tunnel. Contrary to it, realibility probability is the probability of the tunnel to withstand the applied load. As for Safety factor (SF) is a value which represent Resistance flow to Load flow. The ability of tunnel to flow water (hydraulicly) is used for resistance flow and Design water flow (Q2, Q5, Q10, Q25, Q50 and Q100) is used for load flow. To build up the reliability analysis HECRAS and HEC-HMS is a requirement. HECHMS is used to route 13 subcatchment of Citarum River through Nanjung Bridge. While HECRAS is modelled from Nanjung Bridge to 1 km after Curug Jompong. HECRAS uses HEC-HMS output as input to run its simulation. Thus, Nanjung tunnel is reliable for Q2 and Q5 where Q2 is low risk and Q5 is medium risk. As for Q10 to Q100 resulting in very high risk, therefor Nanjung tunnel become not reliable. With the risk level mentioned it is required to maintain and monitor levelling bar, water elevation and current measurement tools, tunnel gate and still basin. Tunnel gate is maintained and controlled for its operation (gate movement) and groundsill is maintained by checking its degredation in still basin. As an addition an extra groundsill need to be placed on upstream and downstream of the tunnel on Citarum River.